Perubahan Perilaku Pola Pinjaman akibat Pinjaman Fintech Online Menggunakan Grounded Theory - Mufti Kusuma Firdaus; Ganang Kartiko Aji; Ahmad Ilham Bachrie Harahap; Jerry Heikal (Journal of Management and Bussines (JOMB), 2025)
This study aims to examine behavioral changes in people's borrowing patterns due to the use of fintech-based online lending services. The research method used was a qualitative approach with grounded theory techniques through in-depth interviews with six respondents consisting of online loan users, lenders, and financial experts, using a snowball sampling technique. The results indicate that behavioral changes are influenced by three main factors: mental health, social impact, and external factors, with external factors such as ease of access, dependency, and utilization of funds having the most dominant influence. The conclusion of this study is that fintech online lending services have shaped consumer behavior patterns and financial dependency in users, primarily due to easy access and minimal financial literacy. Therefore, stronger education and regulation are needed to minimize these negative impacts.   Keywords: Fintech, Behavior Change, Online Lending, Grounded Theory